2018
DOI: 10.1007/s00701-018-3723-5
|View full text |Cite
|
Sign up to set email alerts
|

How I do it: percutaneous transforaminal endoscopic discectomy for lumbar disk herniation

Abstract: BackgroundPercutaneous transforaminal endoscopic discectomy (PTED) has emerged as a less invasive technique to treat symptomatic lumbar disk herniation (LDH). PTED is performed under local anesthesia with the advantage of immediate intraoperative feedback of the patient. In this paper, the technique is described as conducted in our hospital.MethodsPTED is performed under local anesthesia in prone position on thoracopelvic supports. The procedure is explained stepwise: e.g. marking, incision, introduction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…The results we have described showed that PTED was associated with less blood loss, shorter incisions, and shorter hospital stays than fenestration. The postoperative advantages of PTED that we observed are in keeping with other reports [ 16 , 18 ]. For elderly patients, a minimally invasive technique for DLSS that results in fewer iatrogenic injuries may result in faster recovery and easer rehabilitation [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…The results we have described showed that PTED was associated with less blood loss, shorter incisions, and shorter hospital stays than fenestration. The postoperative advantages of PTED that we observed are in keeping with other reports [ 16 , 18 ]. For elderly patients, a minimally invasive technique for DLSS that results in fewer iatrogenic injuries may result in faster recovery and easer rehabilitation [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…With the development of minimally invasive spinal surgery, percutaneous transforaminal endoscopic discectomy (PTED) has become a popular treatment for lumbar intervertebral disc herniation (8) due to its minimal invasiveness, more rapid recovery, and fewer complications (9,10). Posterolateral access can be utilized for a remedy if the procedure fails (11).…”
Section: Introductionmentioning
confidence: 99%
“…The Percutaneous Endoscopic Lumbar Discectomy can be safely performed through a transforaminal, an interlaminar, and a translaminar approach in most cases. There are different commercially available brands each with specific technical caveats 1,3) . The transforaminal approach through Kambin's Triangle is usually done accessing the disc directly.…”
Section: Discussionmentioning
confidence: 99%